Is rumenocentesis a safe technique to collect rumen fluid in dairy cows? - PANOUSIS, N.; KITKAS, G.; VALERGAKIS, G. E. (Journal of the Hellenic Veterinary Medical Society, 2018)
Subacute ruminal acidosis is a major issue in dairy cattle and a definite diagnosis is only established by measuring the rumen fluid pH, most credibly collected by rumenocentesis. However, due to its invasive nature, there is still some debate whether it is a safe method or poses risks for cows’ health and welfare. The aim of the study was to retrospectively evaluate the safety of rumenocentesis as a technique to obtain rumen fluid in dairy cows. Results were derived from 2 studies. In study 1, rumenocentesis was performed in 153 Holstein cows from 12 herds, once, between 10 and 90 days in milk (DIM). In study 2, 83 Holstein cows from a dairy farm were repeatedly subjected to rumenocentesisat 30, 90 and 150 DIM. From the 83 cows that were initially enrolled, 8 were culled before the end of the study for reasons irrelative to rumenocentesis; therefore, 236 rumenocenteses were actually performed in study 2 (3 times in 75 cows, twice in 3 cows and once in 5 cows). All cows were monitored for 10 days after rumenocentesis for presence of complications. In addition, daily milk yield was automatically recorded for each cow in study 2 to detect any possiblepost-rumenocentesis short-term reduction of milk yield. Minor only complications were recorded in 7 cases: in 4/153 (2.61%) and 3/236 (1.27%) rumenocenteses in studies 1 and 2, respectively. Small diameter abscesses in 6 cows (3 in study 1 and 3 in study 2) and a larger one in 1 cow in study 1 were observed. The 3 small abscesses in study 2 were all recorded after the 1st rumenocentesis, at DIM 30. All 7 cases were resolved spontaneously within two weeks. Moreover, short-term daily milk yield of study 2 cows was not affected by rumenocentesis. The conclusion is that rumenocentesis is a safe technique to collect small volume of rumen fluid for SARA diagnosis, which does not compromise cows’ health and welfare when appropriately performed.